The Analysis of the Impact of Cloud Computing-Based Human Resource Information System Implementation on HR Management Efficiency in Multinational Companies - Irene Hasian; Anto Purwadi; Friska Nurliana Sirait (International Journal of Management Science and Information Technology, 2025)
This research examines the effectiveness of a cloud computing-based Human Resource Information System on the efficiency of HRM in MNCs. Cloud computing helps streamline, flex and integrate HR data management and mitigates the dependency on local infrastructure, which is expensive and time-consuming. This application also improve access on real-time data improving synchronization among distributed teams. Adopting a quantitative method and causal descriptive research design, this research incorporated 150 participants, representing 10 multinationals ICTs firms that have embraced the use of cloud-based HRIS. The data was obtained by the means of questionnaires and analysed with the help of descriptive statistics and multiple linear regression analysis. The findings suggest that the adoption of cloud-based HRIS has a positive impact on HRM efficiency in terms of cost efficiency, cycle time reduction, data accuracy and user satisfaction. This indicates that this system provides stronger support of HR management capabilities, especially in the case of MTCS operating in more than one country.